(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article examines the role and interpretation of Gavharshod Beg, one of the Timurid princesses, in historical and artistic works. Not only works of art but also historical works are used in the research process. The study examines the similarities and differences in the depiction of this historical figure. Based on the research, certain conclusions are drawn. Our comments will be presented. Works such as “Ulugʻbek xazinasi”, “Mirzo Ulugʻbek”, “Ona lochin vidosi” serve as objects of our research